Malignant Solitary Fibrous Tumor of the Renal Vein Presenting as a Giant Renal Artery Aneurysm: A Case Report and Review of Literature. (February 2019) - Hertz, Alexandria M.; Childers, Charles K.; Wingate, Jonathan T.; Perry, Jason T.; Kitley, Charles A.; Brand, Timothy C.; Anderson, Mark I.
Objectives . To discuss an unusual presentation of solitary fibrous tumor (SFT) as well as the first description of SFT originating from the renal vein. Case Report . In this article, we report the case of a 56-year-old man who presented with nonspecific epigastric pain and was found on computed tomography to have a large 10-cm renal artery aneurysm with evidence of contained rupture, segmental ischemia of the kidney, and suggestion of renal vein thrombosis. This was treated by a multidisciplinary team of urologists, vascular surgeons, and interventional radiologists with both renal artery coil embolization and radical nephrectomy. The thrombosis was found on pathologic review to be a malignant SFT originating from the renal vein with likely erosion into the renal artery. Conclusion . This report describes the first case of SFT originating from the renal vein and demonstrates the potential for mimicry as a giant renal artery aneurysm.